Riflessioni sui nomi di persona - Vig, István (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*257.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945168);" role="presentation">This <span dir="ltr" style="left: calc(var(–scale-factor)*92.42px); top: calc(var(–scale-factor)*257.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914835);" role="presentation">study examines <span dir="ltr" style="left: calc(var(–scale-factor)*159.62px); top: calc(var(–scale-factor)*257.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983694);" role="presentation">the personal names in Volume III/1 and Volume IV<span dir="ltr" style="left: calc(var(–scale-factor)*377.35px); top: calc(var(–scale-factor)*257.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963795);" role="presentation">/4 of the source publication <span dir="ltr" style="left: calc(var(–scale-factor)*496.18px); top: calc(var(–scale-factor)*257.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912143);" role="presentation">Codice <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*270.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942042);" role="presentation">diplomatico longobardo<span dir="ltr" style="left: calc(var(–scale-factor)*168.02px); top: calc(var(–scale-factor)*270.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921039);" role="presentation">. It aims to discover a) the origins of personal <span dir="ltr" style="left: calc(var(–scale-factor)*353.59px); top: calc(var(–scale-factor)*270.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896071);" role="presentation">names; b) their use in social classes; c) the <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*283.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944829);" role="presentation">language attitude of persons with Longobard names. The bearers of the names were grouped into four social <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*296.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896653);" role="presentation">classes: a) upper class, b) middle class, c) the class of clergymen, d) lower class. (<span dir="ltr" style="left: calc(var(–scale-factor)*109.58px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952286);" role="presentation">As f<span dir="ltr" style="left: calc(var(–scale-factor)*126.98px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944189);" role="presentation">ound in <span dir="ltr" style="left: calc(var(–scale-factor)*160.82px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941758);" role="presentation">royal diplomas, t<span dir="ltr" style="left: calc(var(–scale-factor)*229.25px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928929);" role="presentation">he use of Longobard names in their orig<span dir="ltr" style="left: calc(var(–scale-factor)*393.19px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928437);" role="presentation">inal forms were characteristic <span dir="ltr" style="left: calc(var(–scale-factor)*516.10px); top: calc(var(–scale-factor)*310.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*323.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903114);" role="presentation">members of the upper <span dir="ltr" style="left: calc(var(–scale-factor)*161.66px); top: calc(var(–scale-factor)*323.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900798);" role="presentation">and the middle class<span dir="ltr" style="left: calc(var(–scale-factor)*243.53px); top: calc(var(–scale-factor)*323.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917022);" role="presentation">. The /<span dir="ltr" style="left: calc(var(–scale-factor)*269.81px); top: calc(var(–scale-factor)*323.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903417);" role="presentation">Spoleto/ <span dir="ltr" style="left: calc(var(–scale-factor)*305.81px); top: calc(var(–scale-factor)*323.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916024);" role="presentation">ducal diplomas show a different case: from among the <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*336.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903056);" role="presentation">persons belongin<span dir="ltr" style="left: calc(var(–scale-factor)*139.34px); top: calc(var(–scale-factor)*336.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906944);" role="presentation">g to the upper and middle classes, <span dir="ltr" style="left: calc(var(–scale-factor)*280.13px); top: calc(var(–scale-factor)*336.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922249);" role="presentation">32 persons bear Longobard names in their original forms, <span dir="ltr" style="left: calc(var(–scale-factor)*516.82px); top: calc(var(–scale-factor)*336.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*349.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938081);" role="presentation">addition, <span dir="ltr" style="left: calc(var(–scale-factor)*108.14px); top: calc(var(–scale-factor)*349.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882166);" role="presentation">31 persons bear latinised Longobard names. This <span dir="ltr" style="left: calc(var(–scale-factor)*303.29px); top: calc(var(–scale-factor)*349.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885902);" role="presentation">phenomenon is <span dir="ltr" style="left: calc(var(–scale-factor)*365.71px); top: calc(var(–scale-factor)*349.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894166);" role="presentation">also reflected in their language attitude.) N<span dir="ltr" style="left: calc(var(–scale-factor)*113.42px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.842675);" role="presentation">ames <span dir="ltr" style="left: calc(var(–scale-factor)*136.58px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923027);" role="presentation">of Latin and Greek origins are mainly characteristic <span dir="ltr" style="left: calc(var(–scale-factor)*346.51px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*357.55px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885458);" role="presentation">the lower class, then at a lesser rate <span dir="ltr" style="left: calc(var(–scale-factor)*501.58px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*512.50px); top: calc(var(–scale-factor)*363.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*376.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917302);" role="presentation">clergymen. Surprisingly, they can also be found <span dir="ltr" style="left: calc(var(–scale-factor)*265.01px); top: calc(var(–scale-factor)*376.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923912);" role="presentation">more frequently <span dir="ltr" style="left: calc(var(–scale-factor)*331.63px); top: calc(var(–scale-factor)*376.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.876605);" role="presentation">among the names <span dir="ltr" style="left: calc(var(–scale-factor)*404.11px); top: calc(var(–scale-factor)*376.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922671);" role="presentation">in ducal diplomas. <span dir="ltr" style="left: calc(var(–scale-factor)*106.22px); top: calc(var(–scale-factor)*389.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940816);" role="presentation">The analysis of names and th<span dir="ltr" style="left: calc(var(–scale-factor)*228.89px); top: calc(var(–scale-factor)*389.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950158);" role="presentation">e language attitude of their bearers show a segment of a culturally and <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*402.79px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926033);" role="presentation">linguistically complex society. The members of the upper and middle classes in Northern Italy are characterized <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*415.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933811);" role="presentation">by a positive attitude to the Longobard language and probably by bilingu<span dir="ltr" style="left: calc(var(–scale-factor)*368.23px); top: calc(var(–scale-factor)*415.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918253);" role="presentation">alism, where the dominant language is <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*429.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94599);" role="presentation">Longobard. In the Duchy of Spoleto, <span dir="ltr" style="left: calc(var(–scale-factor)*225.17px); top: calc(var(–scale-factor)*429.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92606);" role="presentation">the members of the middle class and partly those of the upper class were <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*442.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923161);" role="presentation">probably bilingual yet but they tended to <span dir="ltr" style="left: calc(var(–scale-factor)*236.21px); top: calc(var(–scale-factor)*442.39px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958616);" role="presentation">romanity. <span dir="ltr" style="left: calc(var(–scale-factor)*106.22px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882485);" role="presentation">Whereas b<span dir="ltr" style="left: calc(var(–scale-factor)*148.82px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.25021);" role="presentation">ilin<span dir="ltr" style="left: calc(var(–scale-factor)*162.14px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906489);" role="presentation">gualism is probable also among <span dir="ltr" style="left: calc(var(–scale-factor)*292.01px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917293);" role="presentation">clergymen, <span dir="ltr" style="left: calc(var(–scale-factor)*339.31px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*354.07px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953339);" role="presentation">majority of the <span dir="ltr" style="left: calc(var(–scale-factor)*416.47px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906429);" role="presentation">lower class <span dir="ltr" style="left: calc(var(–scale-factor)*463.78px); top: calc(var(–scale-factor)*455.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937104);" role="presentation">are more likely <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*468.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.877054);" role="presentation">to have been <span dir="ltr" style="left: calc(var(–scale-factor)*123.98px); top: calc(var(–scale-factor)*468.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939441);" role="presentation">monolingual<span dir="ltr" style="left: calc(var(–scale-factor)*174.50px); top: calc(var(–scale-factor)*468.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904375);" role="presentation">, using <span dir="ltr" style="left: calc(var(–scale-factor)*203.69px); top: calc(var(–scale-factor)*468.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the s<span dir="ltr" style="left: calc(var(–scale-factor)*222.29px); top: calc(var(–scale-factor)*468.91px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926644);" role="presentation">poken Late Latin.